EFFECT OF ADDITION COCONUT PULP AND BANANA PEEL ON PRODUCTION BIOGAS FROM COW MANURE - Adam Fairuz (The University of Lampung, 2015)
Biogas is a renewable or alternative energy utilizing the decomposition process of awide range of organicwastesthat generates methane gas (CH4). The purpose of this study is to evaluate the effect of the addition of coconutpulp and banana peels on biogas yield from cow dung. Parameters to be observed include: characteristics ofsubstrates, degree of acidity (pH), temperature, biogas production and biogas yield, as well as the flame frombiogas burning. This research is expected to produce an appropriate technology for treating waste of coconutpulp and banana peels into value added products and scientific information on the effect of the addition ofcoconut pulp and banana peels to biogas. The experiment design was a completely randomized design of sixtreatments,with consecutive composition of cowdung : banana peel : coconut pulp namely A50:40:10, B50:30:20,C 50:20:30, D 50:10:40, E 50:0:50, and F 50:50:0 with 3 replications. The data were analyzed by using ANOVAfollowed byDuncan test. The results showed that the additionof coconut pulp and reductionof banana peels in thebiogas composition affected pH, C/N ratio, and biogas production, but had no effect on the temperature, andbiogas yield. The increase in coconut pulp resulted in lower pH, the C/N ratio, and biogas production. Optimumcondition is the treatment with composition of 50:50:0 without the addition of coconut pulp with a C/N ratio of21,22 and pH of 5,5-6,5.Keywords: banana peel, biogas yield, coconut pulp, C/Nratio, renewable energy.